'They are just good people…generally good people': perspectives of young men on relationships with social care workers in the UK. (22nd December 2016) - Featherstone, Brid; Robb, Martin; Ruxton, Sandy; Ward, Michael R.M.
Abstract : The perspectives of marginalised young men on what they value in relationships with social care workers are under‐researched and have not received adequate attention within policy and practice literatures. Moreover, problematic assumptions about gender pervade much political and cultural commentary. Research findings from a study of 50 young men, aged between 16 and 25, attending a range of social care services, are highly significant in this context. They highlight young men's investment in a language of care and respect and their rejection of categorical presumptions. However, the services were steeped in practices and understandings of their marginalisation and offered important opportunities for recognition.